Accumulation of macroparticles on a substrate in vacuum arc titanium plasma; Известия вузов. Физика; Т. 57, № 12, ч. 3 - Ryabchikov A. I. Aleksandr Ilyich; Sivin D. O. Denis Olegovich; Bumagina A. I. Anna Ivanovna; Tupikova O. S. Olga Sergeevna; Shevelev A. E. Aleksey Eduardovich; Usov Y. P. Yuri Petrovich (2014, 2014)
Заглавие с экрана